Legitimacy and Corporate Law: The Case for Regulatory Redundancy - Renee M. Jones (Washington University Law Review, 2009)
This Article provides a democratic assessment of the corporate lawmaking structure in the United States. It draws upon the basic democratic principle that those affected by legal rules should have a voice in determining the substance of those rules. Although other commentators have noted certain undemocratic aspects of corporate law, this Article aims to present a more comprehensive assessment of the corporate regulatory regime. It departs from prior accounts by looking past the states' role to consider the ways that federal regulation shores up the legitimacy of the overarching structure. This focus on the federal role provides some comfort on a democratic account, but also counsels caution with respect to continuing efforts to limit the scope of the federal role within the corporate governance structure. At the federal level, Congress has chosen to regulate corporate matters by setting broad policy objectives and delegating administrative tasks to the Securities and Exchange Commission (SEC). The democratic legitimacy of the corporate regulatory regime thus requires proper respect for the discretion that Congress has vested in the agency. This Article therefore urges skepticism toward efforts to constrain the SEC's regulatory role through judicial challenges to its rulemaking authority. It argues that the agency's ability to respond deftly to market crises and scandals has been hampered unnecessarily by a tradition of aggressive judicial review of agency rulemaking. While rooted in concerns for preserving democratic accountability, this tradition has undermined the very values it seeks to protect. Because the procedures for SEC rulemaking comport well with democratic principles, the agency deserves more deference than courts have been willing to allow. The analysis has implications for current proposals to reform regulation of the national financial markets. Calls to reduce or weaken the SEC's role in financial regulation should give pause to those concerned with the democratic integrity of our regulatory processes. It is the SEC's political independence that bolsters its ability to navigate the rough terrain of regulating the powerful industries within its jurisdiction. Enhancing rather than diminishing the agency's independence should be a central element of proposals to reform our financial regulatory system.
Keywords: Independent regulatory commissions; Deliberative democracy; Judicial deference; Cooperative federalism; United States. Securities & Exchange Commission